Hispanic folk music of New Mexico and the Southwest : a self-portrait of a people - Robb, J. D. (John Donald), 1892-1989 (University of Oklahoma Press, 1980)
First published in 1980 and now available only from the University of New Mexico Press, this classic compilation of New Mexico folk music is based on thirty-five years of field research by a giant of modern music, composer John Donald Robb.